Three new species of Phyllomyza Fallén (Diptera: Milichiidae) from Yintiaoling National Nature Reserve of Chongqing, with an updated key from China - Xi, Yuqiang; Zhu, Yongqiang; Liu, Chang; Yang, Ding; Yin, Xinming (Zootaxa, 2023)
Three species of the genus Phyllomyza Fallén from Yintiaoling National Nature Reserve are described as new to science: P. fuscusagenis sp. nov., P. hirtipes sp. nov. and P. obtususa sp. nov. An updated key to the species of Phyllomyza from China is presented. The specimens are deposited in the Insect Collection of Henan Agricultural University.